Matrix metalloproteinase activation by free neutrophil elastase contributes to bronchiectasis progression in early cystic fibrosis - Garratt, L.W.; Sutanto, E.N.; Ling, K.M.; Looi, K.; Iosifidis, T.; Martinovich, K.M.; Shaw, N.C.; Kicic-Starcevich, E.; Knight, D.A.; Ranganathan, S.; Stick, S.M.; Kicic, Anthony (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2015)
© ERS 2015. Neutrophil elastase is the most significant predictor of bronchiectasis in early-life cystic fibrosis; however, the causal link between neutrophil elastase and airway damage is not well understood. Matrix metalloproteinases (MMPs) play a crucial role in extracellular matrix modelling and are activated by neutrophil elastase. The aim of this study was to assess if MMP activation positively correlates with neutrophil elastase activity, disease severity and bronchiectasis in young children with cystic fibrosis. Total MMP-1, MMP-2, MMP-7, MMP-9, tissue inhibitor of metalloproteinase (TIMP)-2 and TIMP-1 levels were measured in bronchoalveolar lavage fluid collected from young children with cystic fibrosis during annual clinical assessment. Active/pro-enzyme ratio of MMP-9 was determined by gelatin zymography. Annual chest computed tomography imaging was scored for bronchiectasis. A higher MMP-9/TIMP-1 ratio was associated with free neutrophil elastase activity. In contrast, MMP-2/TIMP-2 ratio decreased and MMP-1 and MMP-7 were not detected in the majority of samples. Ratio of active/pro-enzyme MMP-9 was also higher in the presence of free neutrophil elastase activity, but not infection. Across the study cohort, both MMP-9/TIMP-1 and active MMP-9 were associated with progression of bronchiectasis. Both MMP-9/TIMP-1 and active MMP-9 increased with free neutrophil elastase and were associated with bronchiectasis, further demonstrating that free neutrophil elastase activity should be considered an important precursor to cystic fibrosis structural disease.